Pengaruh Ketersediaan, Efektivitas dan Kemudahan Penggunaan QRIS terhadap Keputusan Pembelian : (Studi pada Organisasi GMNI (Gerakan Mahasiswa Nasional Iindonesia) Mojokerto) - Adhe Sarah Ris Dwinomo; Nur Ainiyah; Nurdiana Fitri Isnaini (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This study aims to determine the effect of availability, effectiveness and ease of use of Qris on purchasing decisions. The method in this study uses a quantitative approach with descriptive analysis. The data used is primary data and analyzed using the SemPLS 4 method. The object used is members of the GMNI (Indonesian National Student Movement) organization. The results of this study are partially the availability, effectiveness and ease of use of Qris have an effect on purchasing decisions for members of the GMNI organization.